Young People’s Views on Food Hygiene and Food Safety: A Multicentre Qualitative Study - Rowshonara Syeda; Pia Touboul Lundgren; Gyula Kasza; Monica Truninger; Carla Brown; Virginie Lacroix-Hugues; Tekla Izsó; Paula Teixeira; Charlotte Eley; Noémie Ferré; Atilla Kunszabo; Cristina Nunes; et al. (Education Sciences, 2021)
Foodborne diseases are a global burden, are preventable, and young people are a key population for behaviour change as they gain autonomy. This study aimed to explore young people’s needs across several European countries in relation to learning about and implementing food hygiene and food safety. Qualitative focus groups and interviews were conducted in rural and city regions across England, France, Hungary and Portugal. Data were collected to attain data saturation, transcribed, thematically analysed, and mapped to the Theoretical Domains Framework. Twenty-five out of 84 schools approached (29.8%) participated, with data collected from 156 11–18-year-old students. Students had good knowledge of personal hygiene but did not always follow hygiene rules due to forgetfulness, lack of facilities or lack of concern for consequences. Students had limited understanding of foodborne microbes, underestimated the risks and consequences of foodborne illness and perceived the “home” environment as the safest. Young people preferred interactive educational methods. Addressing gaps in young people’s food safety knowledge is essential to improve their lack of concern towards foodborne illness and motivate them to follow food hygiene and safety behaviours consistently. Findings have been used to develop educational resources to address gaps in knowledge, skills, attitudes and beliefs.